Cenozoic batoids from Contamana (Peruvian Amazonia) with focus on freshwater potamotrygonins and their paleoenvironmental significance - Chabain, Jules (2017)
Among the ichthyofaunal remains collected in the Tertiary deposits of Peruvian Amazonia, elasmobranchs show an unexpected richness of rays, consisting primarily of mostly potamotrygonins (river stingrays), but also pristids (sawfishes) and rhinopterids (cownose rays). Among the Potamotrygoninae subfamily and in addition to the middle Eocene Potamotrygon ucayalensis foundin oldest levels, three new fossil species of Potamotrygon, namely P. contamanensis nov. sp., P. canaanorum nov. sp., and P. rajachloeae nov. sp. are described from late Oligocene-late Miocene deposits along the Quebrada Cachiyacu, near Contamana, Peru. These new fossils fill a substantial gap inthe sporadic fossil record of this exclusive freshwater elasmobranch subfamily, native to South America, thereby highlighting their ancient biological and ecological diversity. In the absence of sharks, the occurrence of obligate freshwater potamotrygonins, along with additional marine to brackish batoidsfrom nine successive fossiliferous levels, supports the predominance of fluvio-lacustrine environments in that region throughout the considered period, with a peak of marine influence around the middle-late Miocene transition, as recorded in other areas of Western Amazonia.